Skull Base Reconstruction with Multilayered Fascia Lata: A Single-Center 17 Years Experience - Ringel, Barak; Abergel, Avraham; Horowitz, Gilad; Safadi, Ahmad; Zaretski, Arik; Yanko, Ravit; Margalit, Nevo; Fliss, Dan M. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Reconstruction after open surgery of anterior skull base lesions is challenging. The fascia lata graft is our workhorse for achieving dural sealing and preventing cerebrospinal fluid leak and meningitis. This study seeks to analyze the donor and recipient site complication rates after fascia lata reconstruction.Methods This is a retrospective review of all open anterior skull base operations in which a double-layer fascia lata graft was used for the reconstruction of the defect from 2000 to 2016 at the Tel-Aviv Sourasky Medical Center, a tertiary referral center in Israel.Results Of the 369 patients operated for skull base lesions, 119 underwent open anterior skull base surgery and were reconstructed with a fascia lata graft. The patients' mean age was 47.1 years, and 68 (57.1%) were males. The overall postoperative early and late donor site complication rates were 6.7% (n = 8) and 5.9% (n = 7), respectively. Multivariate analysis found minor comorbidities and persistent/recurrent disease as being predictors for early-term complications. The overall postoperative early central nervous system (CNS) complication rate was 21.8% (n = 26), while 12.6% (n = 15) of the patients had late postoperative CNS complications.Conclusion Reconstruction of open anterior skull base lesions with fascia lata grafting is a safe procedure with acceptable complication and donor site morbidity rates.
Keywords: skull base; donor site morbidity; fascia lata; complications